The Verb גער “to Exorcize” in Qumran Aramaic and Beyond - Joosten, Jan (Dead Sea discoveries, 2014)
In the Genesis Apocryphon (1Q20 20:28–29) the verb גער “to rebuke” refers to the expelling of an impure spirit. A similar usage occurs in later magical amulets. Developing the hunch of earlier scholars such as Felix Klein-Franke and André Caquot, the present paper argues that the verb גער acquired a specialized meaning “to exorcize” because of the frequent use of Zech 3:2 in exorcisms. The usage is “delocutive”, גער means: “to say: ‘May the Lord rebuke you.’ ”